1999
DOI: 10.1007/s004310051126
|View full text |Cite
|
Sign up to set email alerts
|

Substance misuse in early pregnancy and relationship to fetal outcome

Abstract: This study suggests that one in six women in South London are using drugs in early pregnancy and that cannabinoid use is associated with a poorer pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 23 publications
1
42
0
5
Order By: Relevance
“…Anonymous screening of consecutive urine samples testing positive for pregnancy in a UK inner city demonstrated that approximately 16% of the women were taking illicit drugs [19]. Unfortunately, infants of mothers who abuse opiates antenatally may develop neonatal abstinence syndrome (NAS) and require prolonged treatment and neonatal unit admission.…”
Section: Introductionmentioning
confidence: 99%
“…Anonymous screening of consecutive urine samples testing positive for pregnancy in a UK inner city demonstrated that approximately 16% of the women were taking illicit drugs [19]. Unfortunately, infants of mothers who abuse opiates antenatally may develop neonatal abstinence syndrome (NAS) and require prolonged treatment and neonatal unit admission.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research linking antenatal cannabis use and adverse pregnancy outcomes has been inconclusive (5). A number of studies have reported some adverse effects, including low birth weight (6)(7)(8)(9), preterm birth (7,8,10), small for gestational age (SGA) (7), and small birth length (11,12). However, other studies have disputed these findings (10,(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Limitations include small or highly selected samples (8,12); lack of prospectively collected measures of cannabis use; and lack of control for potential confounders, e.g., socioeconomic status and maternal health, and also use of other substances (cigarettes, alcohol, and other drugs) (7). Cannabis users differ from nonusers in a range of ways and any observed association with ever using cannabis may be indicative of residual or uncontrolled confounding.…”
mentioning
confidence: 99%
“…Special attention should be paid to signs of intrauterine growth retardation (IUGR), microcephaly, prematurity, congenital infection, and major and minor congenital malformations (12). Two of the infants were preterm, none of the infants was small for gestational age.…”
Section: Discussionmentioning
confidence: 99%